Energy its use and the environment - Hinrichs, Roger 1941-; Kleinbach, Merlin H. (Brooks/Cole, Cengage Learning, 2013)
ENERGY: ITS USE AND THE ENVIRONMENT, Fifth Edition, emphasizes the physical principles behind energy and its effects on our environment. The text explains the basic physical principles behind the use of energy, including the study of mechanics, electricity and magnetism, thermodynamics, and atomic and nuclear physics. It also covers crucial environmental questions that currently are receiving much public attention, such as global warming, radioactive waste, municipal solid waste, and nuclear energy production materials.